The Removal of Airborne Severe Acute Respiratory Syndrome Coronavirus 2 (SARS-CoV-2) and Other Microbial Bioaerosols by Air Filtration on Coronavirus Disease 2019 (COVID-19) Surge Units. (30th October 2021) - Conway Morris, Andrew; Sharrocks, Katherine; Bousfield, Rachel; Kermack, Leanne; Maes, Mailis; Higginson, Ellen; Forrest, Sally; Pereira-Dias, Joana; Cormie, Claire; Old, Tim; Brooks, Sophie; Hamed, Islam; et al.
Abstract: Airborne severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) was detected in a coronavirus disease 19 (COVID-19) ward before activation of HEPA-air filtration but not during filter operation; SARS-CoV-2 was again detected following filter deactivation. Airborne SARS-CoV-2 was infrequently detected in a COVID-19 intensive care unit. Bioaerosol was also effectively filtered.